Digital pathology for the primary diagnosis of breast histopathological specimens: an innovative validation and concordance study on digital pathology validation and training. Issue 4 (11th December 2017) - Williams, Bethany Jill; Hanby, Andrew; Millican‐Slater, Rebecca; Nijhawan, Anju; Verghese, Eldo; Treanor, Darren
Abstract : Aim: To train and individually validate a group of breast pathologists in specialty‐specific digital primary diagnosis by using a novel protocol endorsed by the Royal College of Pathologists' new guideline for digital pathology. The protocol allows early exposure to live digital reporting, in a risk‐mitigated environment, and focuses on patient safety and professional development. Methods and results: Three specialty breast pathologists completed training in the use of a digital microscopy system, and were exposed to a training set of 20 challenging cases, designed to help them identify personal digital diagnostic pitfalls. Following this, the three pathologists viewed a total of 694 live, entire breast cases. All primary diagnoses were made on digital slides, with immediate glass slide review and reconciliation before final case sign‐out. There was complete clinical concordance between the glass and digital impression of the case in 98.8% of cases. Only 1.2% of cases had a clinically significant difference in diagnosis/prognosis on glass and digital slide reads. All pathologists elected to continue using the digital microscope as the standard for breast histopathology specimens, with deferral to glass for a limited number of clinical/histological scenarios as a safety net. Conclusion: Individual training and validation for digital primary diagnosis allows pathologists to develop competence and confidence in their digital diagnostic skills, and aids safe and responsible transition from the light microscope to the digital microscope.